Optimalisasi Produksi Pada Industri Tahu Menggunakan Model Linear Programming - Faruk, Ainul (Universitas Islam Madura, 2022)
Tofu is a source of nutrition that is affordable by all people. In addition, processed soybean-based foods are also very popular with the wider community. As for tofu, there are many problems in the problem, one of which is the problem of maximizing the process of making processed soybeans to achieve maximum profit. Therefore, this research was conducted using a linear programming model using the simplex method so that the optimal results obtained from this study were tofu as many as 241 boards and tempeh 250 seeds with a maximum profit of Rp. 1,577,770.